Spermiotoxicity of commercial condoms made from polyurethane, polyisoprene and latex, using domestic ruminants as an experimental animal model. (20th August 2015) - Pradiee, J.; O'Brien, E.; Esteso, M. C.; Castaño, C.; Toledano‐Díaz, A.; López–Sebastián, A.; Santiago‐Moreno, J.
Summary: The use of condoms could provide a means of collecting high‐quality spermatozoa from different species under physiological ejaculation conditions. However, certain condom materials may affect sperm functionality. This study examined the spermiotoxicity of different commercial condom materials towards ram and goat spermatozoa. Sperm samples were diluted in Tyrode's medium and placed in contact with a piece of condom material (polyurethane, polyisoprene or latex) and incubated for 30 or 90 min. Contact time in the polyisoprene and latex treatments affected some sperm variables; no such effects were seen, however, in the polyurethane treatments. For ram spermatozoa in contact with polyisoprene, the percentage of dead spermatozoa with a damaged acrosome increased at 90 min, while for spermatozoa in contact with latex, the percentage of live spermatozoa with an intact acrosome decreased. For goat spermatozoa in contact with both polyisoprene and latex, the percentage of dead spermatozoa with a damaged acrosome increased at 90 min, while for spermatozoa in contact with polyisoprene, the percentage of live spermatozoa with an intact acrosome decreased. In conclusion, latex and polyisoprene contain components that affect sperm motility, plasma membrane integrity and acrosome function. Polyurethane does not seem to reduce the quality of semen.